2013
DOI: 10.1074/mcp.m112.020727
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Hypoxia-inducible Factor 2α Nuclear Interactome in Melanoma Cells Reveals Master Proteins Involved in Melanoma Development

Abstract: Hypoxia-inducible factors (HIFs) are heterodimeric transcription factors that play a key role in cellular adaptation to hypoxia. HIF proteins are composed of an ␣ subunit regulated by oxygen pressure (essentially HIF1␣ or HIF2␣) and a constitutively expressed ␤ subunit. These proteins are often overexpressed in cancer cells, and HIF overexpression frequently correlates with poor prognosis, making HIF proteins promising therapeutic targets. HIF proteins are involved in melanoma initiation and progression; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…Whereas both Sox9 and Sox10 have been identified as HIF target genes (Amarilio et al, 2007;Steunou et al, 2013;Zhang et al, 2011) and are sufficient to produce neural crest cells at least in the trunk neural tube (Cheung and Briscoe, 2003;McKeown et al, 2005), these genes have different expression profiles and functions. Sox9 is transiently expressed in the dorsal neural tube at the neural crest-emigration stages but not required for the emigration per se (Mori-Akiyama et al, 2003).…”
Section: Discussion Hypoxia In Normal Embryogenesis: Species Specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas both Sox9 and Sox10 have been identified as HIF target genes (Amarilio et al, 2007;Steunou et al, 2013;Zhang et al, 2011) and are sufficient to produce neural crest cells at least in the trunk neural tube (Cheung and Briscoe, 2003;McKeown et al, 2005), these genes have different expression profiles and functions. Sox9 is transiently expressed in the dorsal neural tube at the neural crest-emigration stages but not required for the emigration per se (Mori-Akiyama et al, 2003).…”
Section: Discussion Hypoxia In Normal Embryogenesis: Species Specificitymentioning
confidence: 99%
“…The genes that are directly regulated by HIF and expressed in neural crest cells in amniote embryos include SOX9 (Amarilio et al, 2007), SOX10 (Steunou et al, 2013), SNAIL1 (Luo et al, 2011) and CXCR4 (Staller et al, 2003). Although SNAIL2 has not been shown as a direct target of HIF so far, a strong correlation of its expression with hypoxia-induced metastatic phenotypes was shown (Wang et al, 2014;Zhang et al, 2013) [note that chick embryo neural crest cells express SNAIL2, not SNAIL1, whereas in mouse, Snail1 is the gene expressed in the equivalent structures (Locascio et al, 2002)].…”
Section: Hif-1α Mediates the Increase Of Neural Crest Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous pulldown assays have reported that both HIF2α and HIF1β can interact with histone acetyltransferase p300 (68)(69)(70)(71). Indeed, p300 frequently marks enhancers (43) and is thought to be recruited by tissue-specific transcription factors (72).…”
Section: Vhl Restoration Reduces P300 Recruitment But Preserves Promomentioning
confidence: 99%
“…Likewise, affinity purification of tagged EGFR (a cell surface receptor that is overexpressed in a number of cancers) led to the identification and quantification (by isobaric tags for relative and absolute quantification (iTRAQ)-based stable isotope labeling) of differential binding partners in lung tumor cell lines [75]. Several proteins with potentially crucial roles in the development of melanoma were elucidated by AP-MS analysis of hypoxia induced factor 2 (HIF2, a transcription factor commonly overexpressed in aggressive cancers) in human melanoma cell lines [76]. Likewise, novel interactors of the adenomatous polyposis coli (APC) oncoprotein were identified by AP-MS in HEK293 cells [77].…”
Section: Humanmentioning
confidence: 99%